The Transfer of Marine Ship Ownership as an Immovable Object Based on Sale and Leaseback Agreement - Yeni Wijaya; Gunawan Djajaputra (Return : Study of Management, Economic and Bussines, 2024)
Sale and Leaseback agreements  are one of the increasingly popular financing methods in strategic asset management. This agreement is considered to allow the owner of the ship to sell his assets to a third party with an agreement to re-lease the ship for a certain period of time. This method offers financial flexibility, but also presents various legal challenges, particularly related to ownership and certainty of the rights of the parties involved. This study aims to analyze the legal basis, characteristics of agreements, and their implications for the transfer of ship ownership. The approach used in this study is normative with analysis of relevant laws and regulations and case studies. The results of the study show that although  the Sale and Leaseback agreement  provides great benefits in terms of financing, the implementation in Indonesia still faces obstacles, especially for marine capital goods that include immovable objects. In addition, there is a potential for legal disputes if one party fails to fulfill its obligations. For this reason, more detailed legal arrangements are needed to protect the rights and obligations of the parties. This study recommends harmonization between the rules in the field of financing institutions and the rules applicable in shipping as well as stricter supervision of the implementation  of Sale and Leaseback agreements  on ship assets. With adequate arrangements, this agreement can be an effective solution in supporting financing in the shipping sector.